Exploring The Determinan Factor of Nurse Turnover Intention: A Study from Private Hospital - Fitriyati Irviana; Zulia Khozanah Asroriyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study employed a quantitative approach to examine the empirical relationship between supervisor support, occupational stress, work-family conflict, and nurse turnover intention. A survey was conducted among 240 nurses working in a private hospital in Tangerang from March to April 2023. The data was collected using questionnaires that had been validated and reliable, and convenience sampling was used to select the sample. The collected data was analyzed using multiple linear regression. This study employed SPSS version 26 to assess the hypothesis. The result showed that supervisor support has a negative impact on nurse turnover intention. Occupational stress also found to perform a positive effect on turn over intention. In addition, work-family conflict also displays a negative influence on the nurse’ turnover intention. This study suggests a recommendation for a private hotel management regarding maintaining nurses turn over intention by examining the role of supervisor support, occupation stress, and anticipating work-family conflict.